TIPS DAN TRIK PENGELOLAAN KEUANGAN MELALUI KOPERASI SEKOLAH DI SMK AL-FARUQI KAMPAR - Wira Ramashar; Adriyanti Agustina Putri; Nadia Fathurahmi Lawita; Zul Azmi; Siti Rodiah; Della Hilia Anriva; Muhammad Ahyaruddin; Agustiawan Agustiawan; Evi Marlina; Isranbidin Isranbidin (LPPM UMRI, 2018)
This Training and counseling is also intended to provide education about the importance of school cooperation and good financial planning. This activities are carried out in SMK Al Faruqi at Kubang Raya Street, Desa Tarai Bangun , Kecamatan Tambang, Kabupaten Kampar. According to observation result, it is obtained that the school has not a school cooperation, yet. This training and counseling is attended by all participants who are teachers and students. The result shows that the participants have high enthusiasm in describing examples and discussion sessions. The school found this activities are helpful because they get information on how to form a cooperation that has been planned before. So, this cooperation can be useful to this school.